Seǫrita Mariposa - Gundersheimer, Ben (Mister G) Mister; Almada Rivero, Marcos (New York : Nancy Paulsen Books, 2019)
Illustrations and easy-to-read text in English and Spanish follow monarch butterflies on their journey from Canada to Mexico. Includes authors note on how to help protect monarch butterflies.
Keywords: Monarch butterfly -- Migration; Fiction; Butterflies -- Fiction; Monarch butterfly -- Migration; Fiction; Butterflies -- Fiction; Spanish language materials -- Bilingual